The challenges, supports, and strategies of self-directed learning among college students - Cecilia Titiek Murniati; Heny Hartono; Agus Cahyo Nugroho (Journal of Education and Learning (EduLearn), 2023)
In addition to be proficient at their core subjects, college students need to master the 21st-century skills such as critical thinking, collaboration, information literacy, and many other skills. Studies on self-directed learning (SDL) have indicated that SDL is a strong predictor for 21st-century skill mastery. This study aimed at exploring the challenges, supports, and strategies of SDL among college students. This qualitative study used interviews and focus group discussions (FGDs) to obtain data on SDL. The respondents in this study were college students in a private university. The interview and the focus group discussions were then transcribed, analyzed, and coded to find emerging themes. The results of this study indicate several important points. First, social media can empower students in their learning, but can also distract them from their learning. College students needed support from parents, peer groups, and even alumni to seek knowledge independently. Making priorities and maintaining good relationship with classmates, friends, seniors, and alumni are some of the strategies that college students used.